Opportunities and Challenges of Purpose-Led Companies: An Empirical Study Through Expert Interviews - Anette von Ahsen; Kevin Gauch (Corporate Reputation Review, 2021)
Purpose-Led Companies do not exclusively pursue profit-oriented goals, but also orient their actions towards a "higher" purpose. One example of this can be found in contributing to the achievement of social objectives. So far, only a few empirical studies analyze the opportunities and challenges associated with this approach. Accordingly, the present paper examines this approach by means of expert interviews in nine companies. The interview partners evidently believe that, by means of purpose-oriented management, their companies achieve both better financial performance and improved reputation, as well as increased employee motivation. Nevertheless, problems are also identified, in particular the possible trade-offs with profit targets, as well as conflicts due to contradictory stakeholder requirements.
Keywords: 330; Purpose-Led Company; Beyond profit; Corporate purpose